Analysis of Chinese patents associated with incremental clustering algorithms: A review / Archana Chaudhari - Chaudhari, Archana; Mulay, Preeti; Kumar Tiwari, Amit (UiTM Cawangan Perlis, 2022)
With the advent of Internet-of-Things (IoT) and overall Information-Technology world, an enormous amount of data is getting generated dynamically and in real-time mode, in almost all domains of research and application systems. Such huge data has embedded patterns and hidden information to extract and learn. This learning is incremental in nature for all involved entities and users, as the data is growing exponentially in real-time. To achieve learning from such dynamic data sources, incremental clustering algorithms are used mandatorily. This mandate has given rise to increased patents related to incremental clustering concept, which is primarily a significant part of Machine Learning field. In this paper, we contribute to the in-progress discussion on the use of intellectual property resources, particularly patents related to machine learning, incremental clustering, incremental learning with a special focus to country China. Due consideration of the prior art search, the author found that China the country of registration of the application extensively contributes to the intellectual property related to incremental clustering domain hence felt the need to undertake this detailed patent analysis about this topic. We hope all readers, research scholars will be benefited with the latest research presented in this paper pertaining to various patents in the advanced areas of computer engineering.